184 Patient perception of SLE burden: the role of disease activity, comorbidities and treatment. (April 2019) - Elefante, Elena; Tani, Chiara; Ferro, Francesco; Stagnaro, Chiara; Parma, Alice; Carli, Linda; Signorini, Viola; Mosca, Marta
Abstract : Background: Physician-based assessment of SLE activity and damage may not be able to capture the real disease impact on patients life. Objective of our study was to investigate the role of disease activity, comorbidities and treatment in determining patient perception of SLE burden. Methods: This is a cross-sectional study that enrolls patients with a diagnosis of SLE (ACR 1997 criteria). For each patient, demographics, comorbidities, treatment, clinical and laboratory data were collected. Disease activity was evaluated with the SELENA-SLEDAI score and organ damage with the SLICC/DI. The Lupus Impact Tracker (LIT) questionnaire was used to assess SLE impact. The Spearman test has been used for linear correlation between continuous data. Results: We included 195 adult SLE patients (97, 4% Caucasian, 94, 4% female, mean age 44, 212, 8 years, median disease duration 13 years). Median SLEDAI at enrollment was 2 (IQR 0–4) and median SLICC/DI was 0 (IQR 0–2). 9, 8% of patients had a concomitant fibromyalgia. The most frequent active disease manifestations at baseline were hematological (27/195), articular and cutaneous (24/195 both); 13 patients had active renal involvement. 52, 8% of the cohort was on steroid therapy with a mean daily dose of 2, 84, 9 mg of methylprednisolone. 46, 15% was on immunosuppressive treatment and 77, 95% on hydroxychloroquine (HCQ). The median LIT score was 20 (IQR 7, 5–37, 5). Among the LIT items, those with the highest score, suggestive of a severe disease impact, were: anxiety, fatigue and pain. We found no significant correlation between SLEDAI and the score of each LIT item. We found that active articular and cutaneous manifestations, but not renal involvement, influence patient subjective perception of SLE impact. In the multivariate analysis, active arthritis shows a significant correlation with LIT items relative to: pain (p=0, 02), daily activities and future planning (p<0, 01), irrespective of comorbidities. Fibromyalgia resulted associated with a higher score for the item of fatigue (p<0, 01). Finally, we found that also ongoing therapy can contribute to determine SLE burden. In the multivariate analysis, we found a significant correlation between steroid therapy and higher scores for the items of family responsibilities, future planning, discomfort due to physical appearance and drug side effects (p<0, 01), irrespective of disease activity. Conclusions: Disease activity, fibromyalgia and ongoing therapy all contribute to determine SLE burden. In particular, arthritis and skin disease have a great impact on patient daily living. Moreover, steroid therapy negatively influences patient perception of the disease. Funding Source(s): Founding: INTEGRATE project (European Commission, 3rd Health Program, Proposal ID 769736)